A Guerra Illustrada (Typ. da Empreza do Jornal Illustrado ;)
Existências: set. 1918, dez. 1940, mar. 1941, mai. 1941-mai. 1942, julh. 1942, set. 1942, out. 1942, dez. 1942, jan. 1943- abr. 1943, jun. 1943, + (13 exemplares sem data),